Analyzing the combustion and emissions of a DI diesel engine powered by primary alcohol (methanol, ethanol, n-butanol)/diesel blend with aluminum nano-additives. (15th November 2022) - Chen, Qingshan; Wang, Chenfang; Shao, Kun; Liu, Yi; Chen, Xuefeng; Qian, Yejian
Highlight: Nano-Al2 O3 addition increases HRRmax and CGPmax, especially at high engine load. Al2 O3 nanoparticles causes obvious ignition and combustion duration improvements. Nano-Al2 O3 nanoparticles results in the reduction of CO, HC and smoke emissions. Nano-Al2 O3 addition in methanol/diesel blend brings the most appear increment in NOX emission. Abstract: The study investigates the effects of the primary alcohol (methanol, ethanol, n -butanol) and aluminum (Al2 O3 ) nano-additive on combustion and emission characteristics of a direct injection diesel engine at 30% (low) and 80% (high) engine loads of a constant engine speed. The alcohol/diesel nanofuels were made by adding Al2 O3 nanoparticles (25, 100 ppm) into the alcohol/diesel blend (the same oxygen content level) with ultrasonic mixing and surfactant assistance. The results revealed that an extension in the ignition delay was induced by the substitution of primary alcohol fuel, among which methanol showed the most apparent regardless of engine load. Under high load, the addition of methanol in diesel aroused the most obvious promotion effects on peak heat release rate ( HRR max ) and peak cylinder gas pressure (CGPmax ), while under low load, the addition of n -butanol had the most obvious promotion effect. The addition of Al2 O3 nanoparticles to the alcohol/diesel blend significantly improved the combustion process, with the results of decreased ignition delay, increased CGPmax and HRRmax, and shortened combustion duration, especially for the cases in high nanoparticles dosage (with a few exceptions). Under both loading conditions, the addition of methanol led to the least emissions of CO, NOX, and smoke opacity among the three alcohol fuels, while HC emissions presented just the opposite trends. Compared to pure diesel fuel, the engine powered by alcohol/diesel nanofuels emitted less CO, HC, and smoke emissions with a reduction amplitude of 36.2–77.8%, −8.8–10.7%, and 24.2–55.6%, respectively. However, Al2 O3 nanoparticles addition brought more NOX emission with the increment of 6.2–17.5%, especially for the methanol/diesel nanofuels.